Intuition and Reasoning in Choosing Ambiguous and Risky Lotteries - Ralf Bergheim; Michael W. M. Roos (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This paper focuses on information acquisition and individual decision making in ambiguous situations and presents a novel experimental design which may help to tackle open questions from a fresh perspective. Instead of giving subjects the choice between risky and ambiguous Ellsberg urns, we let them choose between a safe option and a risky lottery, whose risk is a priori unknown to subjects. By acquiring information about the probability distribution of the lottery's payoff s, subjects can reduce or even eliminate the ambiguity and turn the decision situation into one of risk. Under the assumption that an ambiguity averse subject should reduce ambiguity within a decision process we predicted that these subjects would request more information. Moreover, we investigate whether the relation between attitudes towards risk and ambiguity is linked to intuitive and deliberate thinking. Based on a detailed analysis of subjects' information acquisition and decision processes we do not find that those subjects showing ambiguity aversion in an urn experiment based on Halevy (2007) significantly reduce the ambiguity more than others. More intuitive subjects acquire less information and are more likely to avoid the risky lottery. Intuition seems to be negatively correlated with risk aversion, but not with ambiguity aversion. Moreover, we find a positive correlation between risk and ambiguity aversion. – – Die experimentelle Studie untersucht den Einfluss von Risiko- und Unsicherheitsaversion auf das individuelle Entscheidungsverhalten. Darüber hinaus wird der Einfluss von intuitivem Denken auf den Entscheidungsprozess betrachtet. Dabei stellt die Studie ein neues experimentelles Design vor, welches hilft, die offenen Fragen auf diesem Themengebiet aus einem neuen Blickwinkel zu betrachten. Anders als in der bestehenden Literatur ist der Grad an Unsicherheit in diesem Experiment endogen und kann durch die Probanden verringert werden. Entscheidungen zwischen einer sicheren Option und eingangs durch Unsicherheit charakterisierter Lotterien können somit durch Informationsgewinnung über die Wahrscheinlichkeitsstruktur der Lotterien zu Entscheidungssituationen unter Risiko verändert werden. Basierend auf detaillierten Analysen des Entscheidungsprozesses zeigen die Ergebnisse, dass Individuen mit höherem Grad an Unsicherheitsaversion, gemessen mit einem Testverfahren nach Halevy (2007), die Unsicherheit nicht signifikant mehr reduzieren als andere. Intuitiv denkende Individuen fragen weniger Informationen nach, vermeiden jedoch risikoreichere Lotterien. Die Studie findet eine positive Korrelation zwischen Intuition und Risikoaversion, aber keine zwischen Unsicherheitsaversion und Intuition. Darüber hinaus zeigen die Ergebnisse eine positive Korrelation zwischen Risiko- und Unsicherheitsaversion.
Keywords: C91; D03; D81; 330; ambiguity aversion; risk aversion; uncertainty; experiment; decision making; binary system of thinking